Effects of straw addition on increased greenhouse vegetable yield and reduced antibiotic residue in fluvo-aquic soil - Zhi-qiang ZHANG; Xiu-bin WANG; Chun-hua LI; Shao-wen HUANG; Wei GAO; Ji-wei TANG; Ji-yun JIN (Journal of Integrative Agriculture, 2015)
Organic manure application is an important measure for high yield and good quality vegetable production, whereas organic manure is also a main source of residual antibiotic in soils. A 3-yr experiment was conducted on a fluvo-aguic soil in Tianjin of northern China. The objective of this study was to investigate the effects of different fertilization patterns on yield of six-season vegetables with celery and tomato rotation, and dynamic change of tetracyclines residues in the soil during the sixth growing season (tomato season). The field experiment comprised six treatments depending on the proportion of nitrogen of each type of fertilizer: 4/4 CN (CN, nitrogen in chemical fertilizer), ¾ CN+¼ MN (MN, nitrogen in pig manure), 2/4 CN+2/4 MN, ¼ CN+¾ MN, 2/4 CN+¼ MN+¼ SN (SN, nitrogen in corn straw), and CF (conventional fertilization, the amounts of nitrogen application were 943 and 912 kg N ha−1 for celery and tomato season, respectively). In addition to CF treatment, the amount of nitrogen application in other treatments was greatly reduced and equal (450 and 450 kg N ha−1 for celery and tomato season, respectively). Results showed that the combined application of ¾ CN+¼ MN achieved the highest yield and economic benefit in the first four seasons, but addition of straw (2/4 CN+¼ MN+¼ SN treatment) performed better in the subsequent two seasons, and the average yields of 2/4 CN+¼ MN+¼ SN treatment were respectively higher by 9.9 and 12.8% than those of 4/4 CN treatment, and by 5.6 and 10.5% than those of CF treatment. The residual chlortetracycline (CTC) in manure-amended soil for three consecutive years increased along with the increase of applied amount of pig manure. Under the same amount of pig manure application, content of CTC in straw-amended soil was obviously decreased compared with no straw-amended soil (¾ CN+¼ MN treatment), and averagely decreased by 41.9% for four sampling periods in the sixth season. Addition of crop straw facilitated the degradation of CTC in manure-amended soil. As a whole, the conventional fertilization was not the desirable pattern based on yield, economic benefit and environment, the optimal fertilization pattern with the highest yield and profit and the least soil chlortetracycline residue was the treatment of 2/4 CN+¼ MN+¼ SN under this experimental condition.